America's bachelor uncle : Thoreau and the American polity - Taylor, Bob Pepperman (American political thought., 1996)
Emphatically revisionist, this book reveals a Thoreau most people never knew existed. Contrary to conventional views, Bob Pepperman Taylor argues that Thoreau was one of America's most powerful and least understood political thinkers, a man who promoted community and democratic values while being ever vigilant against the evils of excessive or illegitimate authority. Still widely perceived as a remarkable nature writer but simplistic philosopher with no real.